Mixing state and light absorption enhancement of black carbon aerosols in summertime Nanjing, China. (1st February 2020) - Ma, Yan; Huang, Congcong; Jabbour, Halim; Zheng, Zewen; Wang, Yibo; Jiang, Youling; Zhu, Wenhui; Ge, Xinlei; Collier, Sonya; Zheng, Jun
Abstract: Direct in-situ measurements of aerosol mixing state, optical properties, and chemical composition were performed in summertime of 2014 at Nanjing, China. Aerosols were predominantly internally mixed, with an average effective density of 1.30–1.63 g cm −3 for 50–230 nm particles, increasing with size. Externally mixed, relatively fresh black carbon (BC) was only episodically observed, with a second mode peaking at 0.51–0.91 g cm −3 . For particles of 110, 140, 185 and 230 nm, BC accounted for 1.7 ± 1.2%, 4.8 ± 3.0%, 5.3 ± 3.3%, and 5.1 ± 3.3% of the particle mass, while being present in 26.4 ± 5.3%, 58.1 ± 27.7%, 59.8 ± 25.4%, and 62.4 ± 27.9% of the particle number concentration, indicating that BC was heavily coated and may contribute significantly to atmospheric aerosol population. Substantial BC absorption enhancement was observed with Eabs of 1.41 ± 0.39, 1.42 ± 0.40 and 1.35 ± 0.38 at 405, 532 and 781 nm, respectively. High volatile aerosol components, in particular nitrate, were found to play vital roles in BC's absorption enhancement. High Eabs values were associated with elevated NOx and RH. A clear diurnal pattern was observed for Eabs supporting a significant impact from traffic emissions, which stood in contrast with previous studies reporting very thin coating and negligible absorption enhancement for traffic emitted BC . High concentrations of NOx co-emitted with BC from traffic sources and its conversion to particulate nitrate likely contributed to the aging and increased absorption of BC particles, which was even enhanced under high RH above the deliquescence point of ammonium nitrate. Therefore, our results indicated that the mitigation of NOx emissions from traffic was critical for reducing the positive radiative forcing induced by BC, especially under high RH conditions. Graphical abstract: Image 1 Highlights: Mixing state, optical properties, and composition of BC were measured in Nanjing. Eabs (BC) of 1.41 ± 0.39, 1.42 ± 0.40 and 1.35 ± 0.38 at 405, 532 and 781 nm were observed. NOx co-emitted with BC from traffics may lead to the BC aging and observed Eabs (BC).